Injection overmolding of polycarbonate-aluminum alloys hybrid structures - Oliveira, Gean Henrique Marcatto de (Universidade Federal de São Carlos, 2023)
Overlap joints between polycarbonate (PC) and aluminum alloys AA6061 and AlSi10Mg were manufactured by injection overmolding and evaluated regarding the interfacial structure and mechanical performance. The injection overmolding parameters; barrel temperature, injection speed and holding pressure were optimized through a design of experiments, using AA6061 inserts machined from an rolled sheet and laser surface textured. The injection molding parameters studied showed a positive effect on the filling of the grooves on the metal surface. The ultimate lap-shear force (ULSF) was used as a response and the values correlated to the filling of the polymer into the grooves of the metal surface, the molding conditions and the rheology of the polymer. Additionally, with the aid of design of experiments, AlSi10Mg inserts were produced by laser powder bed fusion (L-PBF), and their surfaces were structured with submillimetrical dimensions features on the metal surface, so-called, inkpot-like, mushroom-like and lattice structures. Afterwards, the metal inserts were hybridized with PC via injection overmolding and the interfacial strength were evaluated. PC/AA6061 and PC/AlSi10Mg joints exhibited outstanding joining strength of 7.2 MPa ± 0.5 MPa and 20.5 MPa ± 3.8 MPa, respectively. Fracture analysis through optical and scanning electron microscopies and digital image correlation (DIC) was used to elucidate the joint failure mechanisms. In dynamic fatigue testing, joints exhibited fatigue life close to 30% ULSF, demonstrating excellent mechanical durability. In addition, PC/AA6061 joints showed excellent hygrothermal stability. The findings add to the comprehension of the manufacturing, mechanical behavior and durability of injection overmolded polymer-metal hybrid structures.
Sobremoldagem por injeção de estruturas híbridas de policarbonato e ligas de alumínio
Spritzgiessen von hybridstrukturen aus polycarbonatalumium-legierungen
Keywords: Sobremoldagem por injeção; Estruturas polímero-metal; Manufatura aditiva; Policarbonato; Alumínio; Injection overmolding; Polymer-metal hybrid structures; Additive manufacturing; Polycarbonate; Aluminum; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA